Program Kemitraan Masyarakat Bagi Kelompok Kader PKK Desa Barengkok Kecamatan Leuwiliang Kabupaten Bogor - Humaira, Linar (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2019)
The purpose of this community partnership program is to provide knowledge and skills in the utilization of mangosteen peel waste as an active ingredient and natural coloring in making dishwashing soap. The partners in the activity were a group of PKK cadres in Barengkok Village, Leuwiliang District, Bogor Regency. Implementation of activities using counseling, demonstration, training and mentoring methods. Based on the result of the responses of participants in the PKM activites, there was an increase in communityempowerment, namely the knowledge and skills of partners increased in the utilization of mangosteen peel waste. Participants who suggested satisfaction were 72.8% and those who were vey satisfied were 27.2%. The output of this activity is in the form of appropriate technology in the process of making mangosteen skin crusher products and liquid dishwashing solution products based on mangosteen skin extract. Further assistance is still needed for partners who want liquid dishwashing soap products as business products, especially for access to capital, digital based product marketing and business licensing.